The emergence of a technology-based scheme for monitoring and managing remembrance in Al-Quran knowledge - Malik, Rio Andika; Octafia, Sri Mona; Werifmayeni, Annisa; Muzaki, M.Nabil (Lebah, 2025)
Quran memorization education plays an important role in shaping children's character and spiritual intelligence from an early age. To improve the effectiveness of tahfiz learning, a system is needed that is not only harmonious but also manages memorization progress in a structured manner. This community service activity aims to develop a memorization management and monitoring system based on information technology in Early Childhood Tahfiz (TAUD). The main problem faced is the absence of an integrated system that allows comprehensive recording, evaluation, and reporting of memorization progress. The solution offered is the development of a web-based worksheet application that allows students, teachers, and parents to communicate and manage memorization progress in real-time. The methods used include needs assessment, system development, teacher training, application implementation, and evaluation of program success. The results of the evaluation through pre-test and post-test showed an average increase in understanding of +35.33 points for parents and +35 points for teachers after training and use of the system. Mentoring is carried out periodically to ensure continued use of the system. These results indicate that the use of technology can increase the effectiveness of memorization management and parental involvement in supporting children's tahfiz learning